Synthesis of NiAI intermetallic compound as a metal support for solid oxide fuel cells - Opakhai, S.; Kuterbekov, K.A.; Nurkenov, S.A. (Recent Contributions to Physics, 2020)
One of the promising areas of application of porous metals are solid oxide fuel cells on a metal base. Structures with a metal base are of great interest due to the possibility of quick start, greater reliability, mechanical stability, resistance to thermal cycling in comparison with solid oxide fuel cells in which ceramic electrodes or electrolyte are used as the supporting base. In addition, the cost of fuel cells can be reduced by moving to a design in which a porous metal plate performs the supporting function, and the electrolyte and electrodes are deposited in the form of thin films. In most cases, stainless steel is used for the manufacture of supporting metal substrates for SOFCs because they have a coefficient of thermal expansion (CTE) close to that of other components of the fuel cell and high oxidation resistance. However, at high temperatures, a reaction occurs between Fe, Cr from the metal base and Ni from the anode, which leads to a decrease in the catalytic activity of the latter. To solve this problem, the interaction of Cp with Ni is the manufacture of metal bases based on Ni, Ni-Al intermetallic compounds. In this review, we discuss in detail the work of world scientists on the synthesis of Ni-Al intermetallic compounds, especially methods, synthesis thermodynamics, characteristics, process parameters, and reaction features.